Analisis Infrastruktur Tempat Pengelolaan Sampah 3R Berdasarkan Aspek Teknis dan Partisipasi Masyarakat di Desa Abiansemal Kabupaten Badung Bali - Putu Santhi Dharma Gita; I Wayan Runa; I Wayan Parwata (Publikasi Indonesia, 2022)
Abiansemal village has good regional potential to become an agro-tourism village, it can be seen from the area of rice fields and dry fields of approximately 49% of the total area. The impact of this activity is positive and negative. Positive things provide an increase in economic value, but there are negative impacts caused by the increasing amount of waste produced, so it needs proper handling, one of which is making infrastructure for reuse, reduce, recycle waste management (TPS 3R). The purpose of this study is to obtain population projections, waste projections, large community participation in the procurement of TPS3R Infrastructure and present a potential 3R TPS Infrastructure layout model for Abiansemal Village. The method used is descriptive quantitative analysis, in the form of distributing questionnaires for community participation and surveying the characteristics of waste in the technical aspects of the 3R TPS infrastructure. The result of this research is that the waste generation in Abiansemal Village in 2022 is 15.85 m3/day to 18.16 m3/day in 2031. The large participation of the Abiansemal Village community has knowledge, behavior and attitudes that understand, often and agree or in a Likert value percentage above 51% - 75% of the procurement of 3R Waste Management Site Infrastructure (TPS), and a potential infrastructure model as a 3R TPS Abiansemal Village is with a given land area of 1000 m2, the land needed for infrastructure facilities so that they can serve optimally until 2031 with a waste capacity 18.16 m3/day is 514.58 m2, so there is still land left that can be used as other infrastructure to support tourism in Abiansemal Village.